Should State-Owned Firms Change CEOs Before Privatization? The Case of the Telecommunications Industry - Alberto Chong; Virgilio Galdo (Inter-American Development Bank, Research Department, 2003)
Should state-owned enterprises change chief executive officer before privatizing? We test competing views on this question by complementing a recently released database with newly collected data. We are able to cover 77 telecommunications privatizations, which account for nearly 80 percent of the sector in terms of value. We find that CEO replacement will improve performance in the telecommunications industry before privatization as measured by penetration, operating efficiency, and profitability. CEO change before privatization does appear to have real consequences in firm performance before privatization. Moreover, findings are consistent with previous research that links CEO replacement and an increase in privatization prices
Keywords: 330; Öffentliches Unternehmen; Führungskräfte; Privatisierung; Telekommunikationssektor; Welt